Modulation of Clouds and Rainfall by Tropical Cyclone's Cold Wakes. Issue 17 (1st September 2020) - Ma, Zhanhong; Fei, Jianfang; Lin, Yanluan; Huang, Xiaogang
Abstract: Tropical cyclones can pump heat into the ocean by producing a long‐lasting subsurface warm anomaly while leaving a relatively short‐term surface cold anomaly via mixing the upper ocean. Although the heat pumping has been found to be crucial in driving oceanic heat transport and thereby regulating climate changes, the contribution of surface cold anomaly to the atmosphere remains unclear. Here we show that local clouds and rainfall are effectively modulated by cold wakes left behind by tropical cyclones using a combination of satellite observations. On average, the negative surface enthalpy flux anomaly associated with the cold wake results in a reduction of rainfall by 16.6 ± 0.6% (standard error) and a decline of cloud fraction by 6.7 ± 0.4% over the wake region. Clouds and rainfall tend to be more suppressed for slower moving or stronger TCs. With more intense or slower moving TCs in a warming climate, such a modulation could be amplified accordingly. Key Points: The cold wakes left behind by TCs have remarkable feedback effects on the local atmosphere Negative surface enthalpy flux anomaly associated with the cold wake results in a significant reduction in rainfall and cloud activities The suppression of clouds and rainfall depends on the translation speed and intensity of TCs